O grupo reflexivo como dispositivo de aprendizagem docente na educação superior - Pivetta, Hedioneia Maria Foletto (2011)
The focus of this research is in the group as a device for the professors learning in superior education and for their practice. This study is in the Formation Research Line, Knowledge and Professional development of the Post-graduation Program on Education of the Federal University of Santa Maria, Rio Grande do Sul state. The objectives of the study development were: to understand the constitution of a reflexive group as a device for the professors learning in the superior education, to identify the constructive movements of this group, to analyze how the construction of the professors learning occurs from a reflexive group and to investigate that the learning occurs from it. During the development of this thesis it was aimed to answer the following statements: How a reflexive group thought to be a device for learning in the superior education is made? The experience of making part of a reflexive group stimulates the construction of the professors learning? What learning comes from a reflexive group? To answer these questions it was used a qualitative and narrative methodological approach (CLANDININ e CONNELY, 1995). It was developed from fifteen meetings of a group of sixteen professors of a Physics Therapy course from a Confessional Superior Institution in the inland of Rio Grande do Sul state. The instrument for the data collection was a field diary and the professors adopted the class diary as a tool for generating reflection in the group. Another instrument, used as a propellant of the reflection of professors, was their experiences, being these planned and organized for the meetings. The meetings were recorded, written, made unique and categorized for the discursive textual analysis (MORAES and GAGLIAZZI, 2007). The track allowed the identification, at first, of the real group dynamic involving three constructive movements: (1) the initial articulation, (2) approximations and removals and (3) reflexive continuum . For the understanding and the interpretation of this stage, the readings that became references of analysis and understanding are based on Lewin s books (1948; 1965), Ferry (2004; 1976), Josso (2004), Cunha (2006; 2008), Souto (2007) and Oliveira (2009); for the group, Dewey (1976; 1965; 1959) Schön (2000) and Zeichner (1993, 2008); for the reflexive professor, together with Zabalza (2004) e Nóvoa (1992, 2007). The group as a device for the learning is in the description, interpretation and discussion of the categories the emerged from the group: (1) simplification of the professors learning, (2) the manifestation of consciousness about being a professor and (3), the (re)meaning of professors learning. For the discussion about learning how to be a professor, the references of Vygotsky (1995; 1989; 1982), Leontiev (1984), Vygotsky, Lúria e Leontiev (1989), Cunha (2001, 2005, 2006, 2008), Isaia (2006, 2008), Isaia e Bolzan (2007, 2004), Bolzan (2002, 2006) and Maciel (2006) are highlighted. The group is a learning device from the understanding that this learning passes by the personal relations that exist in the superior teaching along with the place where this learning happens. It finishes with the reflection about the elements that are specific and contextual of the superior teaching. The professors learning is, thus, a interpersonal and intrapersonal process which is fruitful in the group context once it happens in a motivational and sharing environment, which promotes transformation in the feeling, in thinking and in acting by the professors.